Designing Orphanage With The Approach Of Creating Sense Of Belonging To The Environment - Khanbabaei, Anahita (The Turkish Online Journal of Design Art and Communication, 2016)
Children how grow up in a family environment with no love and attachment in an unsafe environment would be under emotional, ethical, social and metal crises. Although the crises make same children involved apparently; in deeper concept and in nature, they make whole society involved in it. One of the difficulties of the society is the issue of orphans. These are innocent children who have lost their family under specific conditions and have become orphan forcibly. In fact, orphan children are victims of the society, a society that has not only deprived them from having warm family that is their natural right, but also can't accept them and looks them as scoria. Problems of these children is lack of sense of security and meeting their needs, lack of self-confidence and lack of expressing problems with right person and lack of being loved by others are other shortcomings and mental and behavioral problems of these children. Deprivation of orphans from presence of parents as basic foundations of family system makes challenge for growth of their positive self-concept more than before. Deprivation of natural function of family can affect not only self-concept of orphans, but also it can affect their perception of future. Disappointed child is a child with negative attitude to him/herself and to future and compared to other children, the children experience less safe attachment in relation with a caretaker. However, need to belonging is a comprehensive need. Belonging means that desire to creating a sustainable social relationship and threatening this need in any manner can cause sense of loneliness. In fact, loneliness is a cognitive and emotional reaction to this threat and demonstrates that there is a gap between actual social relationship of person and desired social relationship. In this study, it has been tried to consider important factors to create sense of belonging to the environment in children to design a space for them, so that they can feel to be a member of society and feel less unsafe and alienation with the environment.
Keywords: Sense of Belonging to Environment; Children; Orphan; Family